Working on the street and exposure to violence at work: a study with traffic agents - Selma Lancman; Laerte Idal Sznelwar; Seiji Uchida; Tatiana Amadeo Tuacek; Agnes Ann Puntch (Faculdade de Medicina de Botucatu (Unesp), 2007)
This study was done with transit agents, who for various reasons related to the organization of their work and the fact that the street is their work space, are exposed to situations of intense verbal, and sometimes physical, aggression. By studying this situation it is hoped to make a contribution to understanding the impact of violence on the mental health of workers who work on the streets and its reflections in their health, their work development and relationships. This study was based on theoretical/methodological principles of the psychodynamics of work. This is a reserach-action method in which doing research presupposes having a transformative action on the situation studied. We verified that living with violence in the exercise of their profession has a strong impact on workers' mental health on the one hand, and on the other, they develop strategies and use work-related intelligence in order to be able to continue working.